Working in Danish ice hockey: Psychological services derived from the context - Larsen, C. H. (Journal of Sport Psychology in Action, 2018)
This article describes my experiences of working in Danish national junior ice hockey. I will describe the professional philosophy underpinning my services in ice hockey and I will outline the psychological services provided for the Danish junior national team that are derived from the context. In terms of identifying psychological areas of development, I used information from multiple sources, including the coaches, staff, players, and also observations of practice and competition. Three different but connected areas were targeted with the junior national team. First, creating an understanding and acceptance of roles within the team. Second, developing effective team communication under pressure. Third, learning the ability to register thoughts, release thoughts, and refocus under pressure. I then make conclusions by reflecting upon the effectiveness of services for the junior national team and the lessons learned from them.